Indus Valley : green lessons from the past - Sen, Benita (New Delhi The Energy and Resource Institute, 2017)
Did you know that as many as 7000 years ago, people who lived in the Indus valley practised rainwater harvesting? Not only that, this smart green civilization also used sun-baked bricks, which was an effective way to use solar energy. Familiarize yourself with the fascinating ways of this ancient civilization as Teri, our time-travelling explorer, goes back in time, to the Indus Valley.
Keywords: Green movement; Indus civilization